Atrial fibrillation and cognitive function: a case control study - ROBERTSON, IAN (My University, 2005)
Atrial fibrillation is an important and independent risk factor for cerebrovascular disease and vascular dementia. There is increasing evidence that atrial fibrillation is associated with an increased risk of asymptomatic or silent cerebral infarction and as a result may confer an increased risk of progressive cognitive impairment on a person. In this study we sought to determine whether this hypothesis could be explored in a prospective case controlled design. Twenty seven patients with non-valvular atrial fibrillation (NVAF) and no history of stroke, transient ischaemic attack, dementia, and thyrotoxicosis were compared with 54 age and sex matched controls in sinus rhythm. All cases underwent clinical examination, ECG, and psychological assessment using a battery of nine neuropsychological tests. Between group analysis and a comparison of mean test scores of paired controls with cases were undertaken. The presence of atrial fibrillation was consistently associated with poorer performances on all the subtests of the neuropsychological battery. There was no association between duration of atrial fibrillation and performance. These results provide evidence to justify further examination of the hypothesis in a larger prospective study to determine whether antithrombotic therapy may protect against cognitive decline in patients at maximal risk of silent cerebral ischaemia and associated cognitive decline.
PUBLISHED
Keywords: Neuropsychiatry